(The relations of the Salafist state with the forces neighboring Persia (543-685 AH / 1148-1288 CE - Al Thaqafi, Ahlam Ahmed (Journal of Humanities & Social Sciences, 2017)
In the Seljuk state, Persia was subject to the Seljuks. subordinate to them, governed by their deputies, Fares ruled during the Seljuk era several Atabakk such as Roknuddin Khmartkin, and then Jauli Sakao, and after His death took Maknobers the reign, then Buzaba who was killed by Sultan Masoud Seljuki. The Salafist state that ruled Persia was subject to the powerful states of the region at the time At the beginning of its command the Seijuks were subject to their independence from them, which appeared through some Events, and then after the weakness Of the Seljuk State. and the disintegration and emergence of the State algorithm (551 e / 1056 m) The State underwent a Strong algorithm, and its relationship was subordinated, subordinate. and then followed the appearance of invasion Mughai (628 AH / 1231 AD), and its expansion and spread and its impact on the State of Khwarizmin, the Mongols The invasion Of the Islamic world and the overthrow Of Baghdad in 656 AH (1258 CE), and it appears that the Salafist state was held With the Mongols a treaty stipulating that Persia would not be endangered in return for the payment Of annual royalties to Elkhan Mughal, and then developed this treaty to the intervention of the Mongols in the policy of the Salafist State, until it controlled After the Saigren became rulers by name only on Persia, and were subject to the real Mughai state controlling the affairs Of Persia. The problem of the research is to clarify the relation Of the Salgarian to the force controlling the region during their rule for Persians starting with the Seljuks and Attabikat of them and then the relationship between the Salgren Khwarzmin and to review their relationship with the Mongols. The Seljuks and the Atabkiyat affiliated with them, and then the relationship between the Salgarians and the Khwarizmians This study is based on historical research methodology based on the collection of scientific material from its sources Original and modern references, and ensure its credibility in research and survey, and presentation of the method of criticism In order to reach the most historical facts and use them in a scientific way,